Dieneremia rueckeri, a new genus and species of minute brown scavenger beetle from Baltic amber, with notes on other fossil Latridiidae (Coleoptera: Cucujoidea) - Reike, Hans-Peter; Alekseev, Vitaly I.; Bukejs, Andris (Zootaxa, 2013)
Dieneremia rueckeri gen. et sp. nov. is described and illustrated from Upper Eocene Baltic amber (Yantarny village, the Kaliningrad Region, Russia). A new synonymy is established: Latridius jacquelinae Hawkeswood, Makhan and Turner, 2009 = Latridius jantaricus Borowiec, 1985. New fossil records on Latridius jantaricus Borowiec, 1985 are presented.